Deciphering chemical diversity among five variants of Abeliophyllum distichum flowers through metabolomics analysis - Yeong‐Geun Lee; Jeong Eun Kwon; Won‐Sil Choi; Nam‐In Baek; Se Chan Kang (Plant Direct)
Abstract Abeliophyllum distichum (Oleaceae), endemic to the Korean Peninsula and the sole member of its genus and species, possesses high scarcity value, escalating its importance under the Nagoya Protocol. Despite its significance, their metabolites and activities of A. distichum flowers remain unexplored. This study employs an integrated metabolomic approach utilizing NMR, LC/MS, GC/MS, and FTIR techniques to comprehensively analyze the metabolite profile of A. distichum flowers. By combining these methods, we identified 35 metabolites, 43 secondary metabolites, and 108 hydrophobic primary metabolites. Notably, distinct concentration patterns of these compounds were observed across five variants, classified based on morphological characteristics. Correlation analyses of primary and secondary metabolites unveiled varietal metabolic flux, providing insights into A. distichum flower metabolism. Additionally, the reconstruction of metabolic pathways based on dissimilarities in morphological traits elucidates variant‐specific metabolic signatures. These findings not only enhance our understanding of chemical differences between varieties but also underscore the importance of considering varietal differences in future research and conservation efforts.